BAHASA PEREMPUAN PADA CERPEN CERITA PENDEK TENTANG CERITA CINTA PENDEK KARYA DJENAR MAESA AYU - Zulkurnain Nashr, Basuki (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2015)
This study is a phenomenon which is reflected in a work of fiction and their meaning in women's language. Data collection techniques in this research is to use Docs. Untu data analysis techniques to analyze this research is an interactive mode. Based on the results of the discussion in women's language research on the short story collection "Short Story About Love Story Short" Maesa Ayu Djenar work can be summed up as beikut. Vocabulary and ideology of women all have in theory perjuanagn ideology of women, has been applied in the short story collection "Short Story About Love Short crita" Djenar work Maesa Ayu. vocabulary produced by the women, but in the selection of that vocabulary terseliplah a struggle of women. gramtika various ideologies applied neatly all of each title capable of representing the theory.